STUDI ETNOBOTANI TUMBUHAN OBAT PADA MASYARAKAT SUKU MANDAR DI DESA SARUDE SARJO KABUPATEN MAMUJU UTARA SULAWESI BARAT - Rusmina H. Z.; Miswan Miswan; Ramadhanil Ramadhanil (Biocelebes, 2015)
The research entitled “Ethnobotanical Study of  Plant Medicine on Mandarese Society in West Sulawesi Indonesia” has been carried out from April to June  2012  at the Sarjo, a village of  Mandarese which is located in North Mamuju regency of West Sulawesi Province. The objective of the research was to collect data of medicinal plant species that used by the Mandarese people for their daily lives especially to  ttreatment of various diseases and health maintenance. The basic data of medicinal plants  has been collected by using  direct interview to village leaders, religious leaders, traditional healers, and government officers These interviews were recorded with audio recorders and  notebooks. Photographs were also taken to record information. All of plant materials used for this purpose collected in the field and then  identified at the Herbarium Celebense (CEB) Tadulako University. The observation was included vernacular name, scientific name, family,  habits, uses and technique and samples processing. Data analyzed by using formula of  knowledge percentase analyzes of medicinal plants  (Sunarno et al. 1991).  The result showed that there were 50 (fifty) plants species belong to 28 families utilized as medicine. Zingiberaceae, Arecaceae, Solanaceae and Piperaceae were the dominant plant family were used by them. The  organ of plants such as leaves, stems, roots, fruits, rhizomes and some were used as a whole or separately. Keywords: Plant medicine, Ethnobotany Study, Mandarese, Sarjo, West Sulawesi Indonesia